The Interaction Effect of Accounting Information Systems User Satisfaction and Activity-Based Costing Use on Hotel Financial Performance: Evidence from Greece - Ioannis Diavastis; Evgenia Anagnostopoulou; Georgios Drogalas; Theofanis Karagiorgos (Journal of Accounting and Management Information Systems (JAMIS), 2016)
The interaction of Information Technology (IT) and contemporary management accounting systems is an emerging research area. This paper aims at exploring the interaction effect of Accounting Information Systems (AIS) user satisfaction and Activity-Based Costing (ABC) use on hotel financial performance. We empirically test the above relationship in Greek hotel industry, because its highly competitive and information-intensive nature is characterized by the necessity for useful and accurate cost accounting information. Using hierarchical regression analysis, results suggest that when ABC use interacts with AIS user satisfaction, hotel financial performance is improved. On the contrary, AIS user satisfaction and ABC use have no significant association with financial performance when they act independently. This study fills a gap in the literature by developing a new framework that combines IS user satisfaction theory (IS Success Model) and contemporary management accounting techniques. Moreover, it underlines the role of AIS user satisfaction as an enabler of ABC. Finally, our findings extend the hospitality accounting literature, since empirical research on ABC is limited in the hotel industry.
Keywords: M41; M15; L83; 650; accounting information systems; user satisfaction; Activity-Based Costing; financial performance; hotels